Laterally Displaced Pedicle Flap for the Management of Localised Gingival Recession: A Case Report - Shahi, Kripa; Aryal, Deepa; Shrestha, Surendra Man (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Gingival recession, whenever presents with sensitivity, aesthetic problem, root caries or difficulty in plaque control may pose a challenge for clinicians. Among the various treatment modalities for root coverage, laterally displaced flap has been a promising treatment for isolated gingival recession with an adequate amount of donor tissue adjacent to the recipient site. This case report presents a case of successful root coverage where laterally displaced flap was employed for the management of gingival recession in mandibular central incisor with two and a half years follow up.